HUBUNGAN KONSUMSI GLUTEN DAN KASEIN DENGAN PERTUMBUHAN SERTA PRESTASI AKADEMIK ANAK PADA SEKOLAH LUAR BIASA DAMAI DI KOTA TOMOHON - Mirna Kawulusan; Vera T. Harikedua; Daniel Robert (POLTEKKES KEMENKES MANADO, 2014)
Child growth include the growth and development of organs cells. Growth is measuredby the physical dimensions of the present picture of the state of nutrition. Growth can beused as an indicator of the adequacy of inputs of nutrients essential because it can bemeasured by the volume of the child's weight gain. Motor development is a process thatmust be passed in a child's life. One of the child's motor skills are gross motor skillsrelated to movement skills that are affected by the large muscles such as : standing,walking, running and jumping. Learning is a process of the work done for someone toacquire a new behavior changes as a whole as his own experience in the interactionwith the environment. Learning means filling activities or the development of cognitiveabilities with the fact that as many students mastered.Survey research methods used (non-experimental) with the cross-sectional design.Exceptional location at the School of Peace in Tomohon is from August to October2013, amounting to 40 students. Statistical analysis used were t - test and Pearson'scorrelation test.Results The average intake of gluten students as much as 247.50 g, average 19.75 gcasein intake, correlation test showed no association between gluten intake in growingchildren (p= 0.881), there was no association between gluten intake with academicachievement children (p= 0.411), there was no correlation between casein intake withgrowth of children (p= 0.319 ), and there is a relationship between the intake of caseinto academic achievement (p= 0,04)